2021
DOI: 10.29333/iji.2021.14234a
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Motivated Strategies for Learning Questionnaire: Comparison of Three Competing Models

Abstract: Students who are self-regulated leaners have been reported to perform more successfully in higher education institutions (HEIs). Therefore, instruments that can monitor students' motivation and learning have been devised and implemented. The aims of this work were to investigate the dimensionality of the motivated strategies for learning questionnaire (MSLQ) and compare the validation of the three competing models. Three competing measurement models (1-factor, 2-factor, and second-order factor) were selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…The findings indicated that the ten aspects-including online self-efficacy, intrinsic motivation, extrinsic motivation, online negative achievement emotions, planning and time management, metacognition, learning environment, effort regulation, online social support, and ten online task strategies-were useful and valid. Khampirat [34] validated SRL instrument using three different methods. Furthermore, the instrument analyzed was the motivated strategies for learning questionnaire (MSLQ).…”
Section: Resultsmentioning
confidence: 99%
“…The findings indicated that the ten aspects-including online self-efficacy, intrinsic motivation, extrinsic motivation, online negative achievement emotions, planning and time management, metacognition, learning environment, effort regulation, online social support, and ten online task strategies-were useful and valid. Khampirat [34] validated SRL instrument using three different methods. Furthermore, the instrument analyzed was the motivated strategies for learning questionnaire (MSLQ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional analysis from further studies revealed that the Composite Reliability (CR) surpassed the Average Variance Extracted (AVE), and the AVE exceeded 0.5, suggesting a strong convergence validity among the subscales ( Buratin, 2021 ). The target coefficient for comparing the first-order and second-order factor models was 96.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Pelatihan Berdasarkan hasil penelitian terhadap motivasi 31 peserta mengikuti program pelatihan, 10 persen peserta memiliki motivasi tinggi; 79 persen memiliki motivasi sedang; dan 11 persen memiliki motivasi rendah. MSLQ (Motivated Strategies for Learning Questionnaire) adalah sumber data motivasi ini, yang mencakup pengidentifikasi identitas, nilai aktual, stres akademik, penggunaan strategi kognitif, dan pengaturan diri (Irvine & Williams, 2022;Khampirat, 2021;Tejani et al, 2021;Zhou & Wang, 2021). Motivasi pelatihan terhadap kinerja sangat berdampak (Halim, 2022;Nolisa & Edalmen, 2021;Wahyudi, 2021).Efektivitas mengajar juga dipengaruhi oleh kualifikasi dan pelatihan guru (Putri et al, 2022).…”
Section: Gambar 1 Dokumentasi Kegiatan Pengabdian Masyarakatunclassified